2012
DOI: 10.1111/j.1399-3054.2012.01705.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated CO2 and temperature on photosynthesis and leaf traits of an understory dwarf bamboo in subalpine forest zone, China

Abstract: The dwarf bamboo (Fargesia rufa Yi), growing understory in subalpine dark coniferous forest, is one of the main foods for giant panda, and it influences the regeneration of subalpine coniferous forests in southwestern China. To investigate the effects of elevated CO 2 , temperature and their combination, the dwarf bamboo plantlets were exposed to two CO 2 regimes (ambient and double ambient CO 2 concentration) and two temperatures (ambient and +2.2 • C) in growth chambers. Gas exchange, leaf traits and carbohy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 49 publications
(109 reference statements)
1
20
1
Order By: Relevance
“…Dwarf bamboo-dominated forests are often subject to extreme temperature and rainfall patterns as a result of climate change, which exposes them to temporary periods of drought during their life cycle and then adversely affects their growth (Wang and Ma, 1993). Fargesia rufa Yi, one of the most important dwarf bamboos, is distributed abundantly in floors of subalpine forests of China (Li et al, 2013). More importantly, it is the staple food for the endangered giant pandas.…”
Section: Introductionmentioning
confidence: 99%
“…Dwarf bamboo-dominated forests are often subject to extreme temperature and rainfall patterns as a result of climate change, which exposes them to temporary periods of drought during their life cycle and then adversely affects their growth (Wang and Ma, 1993). Fargesia rufa Yi, one of the most important dwarf bamboos, is distributed abundantly in floors of subalpine forests of China (Li et al, 2013). More importantly, it is the staple food for the endangered giant pandas.…”
Section: Introductionmentioning
confidence: 99%
“…was assayed by homogenization of 0.2 g frozen leaves in 2 mL 10 % HCl and determined by colorimetric method (Tang 1999). Reduced N was determined by microKjeldahl method after digestion in H 2 SO 4 -H 2 O 2 (Li 2000). Total N was defined here as the sum of NO 3 -and reduced N (Sánchez-Rodríguez et al 2011).…”
Section: Biochemical Analysismentioning
confidence: 99%
“…NO 3 -was analyzed from an aqueous extraction of 0.2 g frozen leaves in 5 mL of deionized water for 10 min in a boiling water bath and measured at 410 nm (Li 2000). NH 4…”
Section: Biochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorophyll content decreased with the accumulation of non-structural carbohydrate under elevated CO 2 concentration and temperature. Li et al (2013) found that starch particles accumulate in the chloroplasts of the dwarf bamboo growth under elevated CO 2 concentration. Non-structural carbohydrate accumulation is generally thought to physically distort the chloroplast (DeLucia et al 1985) and possibly hinder CO 2 diffusion within the chloroplast (Makino 1994).…”
Section: Leaf Chlorophyll Contentmentioning
confidence: 99%